"Water-like" ammonium-based ionic liquids for lipase activation and enzymatic polymerization. (November 2020) - Zhao, Hua; Toe, Christopher
Graphical abstract: Highlights: "Water-like" ammonium-based ionic liquids were synthesized. Dual-functionalized ionic liquids are highly compatible with the lipase. Lipase in "water-like" ammonium-based ionic liquids showed high thermal stability. Enzymatic polymerization of ε-caprolactone produced high M w and yields. Abstract: Novel dual-functionalized ammonium-based hydrophobic ionic liquids (ILs) have been synthesized by mimicking the water structure to carry both ether group (hydrogen-bond acceptor) and tert -alcohol group (hydrogen-bond donor). These ammonium-type ionic solvents exhibit the advantage of lower viscosities (as low as 129 mPa s at 30 °C) than the imidazolium analogue (∼300 mPa s at 30 °C); more importantly, these "water-like" media are highly compatible with immobilized Candida antarctica lipase B (Novozym 435) in terms of producing high transesterification activities (1.5-fold higher than that in tert -butanol, and slightly higher than that in diisopropyl ether) and higher thermal stability than that in tert -butanol. To demonstrate the utilization of this new solvent system, enzymatic ring-opening polymerization (ROP) of ε-caprolactone using these "water-like" ILs as co-solvents was carried out to synthesize polyesters, achieving high molecular mass M w (up to 18, 000 Da) and high yields (up to 74 %).